ELISA Test for the Serological Detection of Scedosporium/Lomentospora in Cystic Fibrosis Patients - Martin-Souto, Leire; Buldain, Idoia; Areitio, Maialen; Aparicio-Fernandez, Leire; Antoran, Aitziber; Bouchara, Jean-Philippe; Martin-Gomez, Maria Teresa; Rementeria, Aitor; Hernando, Fernando L.; Ramirez-Garcia, Andoni (Frontiers in Cellular and Infection Microbiology, 2020)
The detection and diagnosis of the opportunistic fungi Scedosporium spp. and Lomentospora prolificans still relies mainly on low-sensitive culture-based methods. This fact is especially worrying in Cystic Fibrosis (CF) patients in whom these fungal species are frequently isolated and may increase the risk of suffering from an infection or other health problems. Therefore, with the purpose of developing a serologic detection method for Scedosporium/Lomentospora, four different Scedosporium boydii protein extracts (whole cell protein extract, secretome, total cell surface and conidial surface associated proteins) were studied by ELISA to select the most useful for IgG detection in sera from CF patients. The four extracts were able to discriminate the Scedosporium/Lomentospora-infected from Aspergillus-infected and non-infected patients. However, the whole cell protein extract was the one selected, as it was the one with the highest output in terms of protein concentration per ml of fungal culture used, and its discriminatory capacity was the best. The ELISA test developed was then assayed with 212 sera from CF patients and it showed to be able to detect Scedosporium spp. and Lomentospora prolificans with very high sensitivity and specificity, 86%–100% and 93%–99%, respectively, depending on the cut-off value chosen (four values were proposed A450nm= 0.5837, A450nm= 0.6042, A450nm= 0.6404, and A450nm= 0.7099). Thus, although more research is needed to reach a standardized method, this ELISA platform offers a rapid, low-cost and easy solution to detect these elusive fungi through minimally invasive sampling, allowing the monitoring of the humoral response to fungal presence.